De estetiska ämnenas didaktik Utmaningar, processer och protester - von Schantz, Ulrika; Thorgersen, Ketil; Lidén, Anne (Stockholm University Press, 2018)
This anthology presents perspectives on teaching and learning in the arts and is relevant for teachers and teacher students in the arts as well as researchers and PhD candidates. The analytical discussions about children, pupils, teachers and students in varying forms of creative education is treated from a variety of theoretical perspectives and offers new ways of thinking about the arts in all forms of education. In the anthology, researchers, senior lecturers and experienced educators discuss research questions about aesthetic expressions, communication, subjects, learning processes and reflections from a practice point of departure. The authors are all employed at or connected to the arts education at the Department of Humanities and Social Sciences Education (HSD) at Stockholm University, Sweden. The book includes descriptions of different research practices such as research by professors and senior lecturers, post docs as well as the reflective writings of teaching personnel. The chapters have all gone through a double-blind peer-review process.